Vloga državljanstva v politikah integracije imigrantov v izbranih državah članicah Evropske unije - Kejžar, Barbara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
The role of citizenship in immigrant integration policies in selected EU member states. The article offers insight into the interconnection of two important concepts of today's modern society: citizenship and the integration of immigrants. The author in the context of a comparative analysis of citizenship policies in selected European countries (including Slovenia) pursues two goals: firstly, to identify the characteristic elements of these policies and to establish, if they follow the trends of convergence and liberalization of policies, which are recognised at the global level; secondly, to determine what role these policies have in the context of the integration process of immigrants in receiving societies. Does citizenship appear only as a reward for successful completion of a process of immigrant's integration into receiving society or does it appear as an incentive factor already in the course of this process? The author on a basis of the analysis identifies certain trends of liberalization and convergence of citizenship policies in selected European countries, but at the same time points to the continuing importance of diversity of national arrangements. She also notes that citizenship policies to some extent already shape comprehensive approaches to the problem of integration of immigrants into receiving society.But currently citizenship remains only a promised reward for a successful performance at the test, which indicates a sufficient degree of integration into receiving society, and it still does not appear as an incentive factor to facilitate the integration into receiving society.
Keywords: European Union; Evropska unija; imigranti; državljanstvo; integracija